JENIS BIVALVA DI SUNGAI KAMPAR KANAN KELURAHAN AIR TIRIS KECAMATAN KAMPAR KABUPATEN KAMPAR - Wilda Mardiyah; Nur El Fajri; M Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
In the Kampar Kanan River there are activities that affect the water quality in general and affect the abundance bivalve. To understand the abundance of bivalve in that river, a study has been conducted in February to March 2017. Parameters meansured were types and abundance of bivalve, temperature, depth, turbidity, current speed, pH, dissolved oxygen, nitrate and phosphate concentration. Relationship between bivalve abundance and organic material content was analyzed using a simple linear regression. Result shown that there were 5 bivalve spesies present, namely Anadonta woodiana (11/m2), Corbicula moltkiana (33/m2), Hyriopsis sp (4/m2), Pilsbryconcha exilis (10/m2) and Rectidens sp (3/m2). Consentration of organic material content in the sediment was 7.07 – 24.35%. There was strong relationship between bivalve abundance and organic material content (99.18%).Keywords: Bivalve, Kampar Kanan River, Organic Matter, Sedimentary Fraction